Separation of neutralizing and hemagglutination-inhibiting antibody activities and specificity of antisera to sodium dodecyl sulfate-derived polypeptides of polyoma virions. - Bolen, J B (1980)
Antisera to the sodium dodecyl sulfate (SDS)-polyacrylamide gel-derived polyoma virion polypeptides were used in immunoprecipitation experiments with ethylene glycol-bis-N,N'-tetraacetic acid (EGTA)-dissociated polyoma virions and capsids to determine the specificity of the antipolyoma polypeptide sera. Additionally, a technique for applying 125I-labeled immunoglobulins to SDS-polyacrylamide gels was used to explore the antigenic specificities of the antisera. The results demonstrated that antisera directed against the SDS-gel-derived VP1, VP2, and VP3 did not react with native polyoma proteins, but would react with the appropriate antigens on denatured polyoma proteins. Antisera against the histone region of such gels reacted with native and denatured polyoma VP1. Separation of neutralizing antibodies from hemagglutination inhibition (HAI) antibodies to polyoma in antisera directed against the histone region of polyacrylamide gels was done by using a polyoma capsid affinity column. The antibodies eluted from this column which did not react with capsids possessed only neutralizing activity, whereas antibodies which bound to capsids possessed only HAI activity. These isolated immunoglobulin G fractions were then used in immunoprecipitation experiments to demonstrate that the antigenic determinants responsible for the HAI activity of the serum were contained on a 16,000-dalton polypeptide, whereas those antigenic determinants responsible for neutralizing activity were contained on a 14,000-dalton polypeptide. Both of these polypeptides present in the histone region of the SDS-gels appeared to be derived from the major virion protein VP1.